Characterization and preparation of higher photon number states - Silberhorn, C; Achilles, D; U'Ren, AB; Banaszek, K; Walmsley, I (2004)
The ability to create and characterize photon number states is of utmost importance in most optically-implemented quantum information schemes. In the past, progress in this area has been hindered by a lack of photodetectors that are both highly efficient and can discriminate different photon number states. We have utilized a time-multiplexed detector to characterize the properties of a heralded photon source based on parametric downconversion. We also show that the different losses in our detector can be described by a single loss parameter, greatly simplifying the data analysis.